PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING DIPADU STUDENT FACILITATOR AND EXPLAINING TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA KELAS X SMAN 6 KEDIRI PADA POKOK BAHASAN FUNGI - M. Agung Setiawan (UNIVERSITAS PGRI MADIUN, 2017)
Kingdom Fungi material is material to learn about mushrooms. In the Kingdom Fungi consist of six phylum that zygomycota, Ascomycota, Basidiomycota, Deuteromycota, Lumut crust, and Mycorrhiza. The material has many types of fungi kingdom, scientific name, and classification of fungi that constrain students to memorize and understand that students need learning model that can provide a good learning experience. This study aimed to determine the effect of learning model combined Student Problem Based Learning Facilitator And Explaining the ability of critical thinking on the matter Kingdom Fungi in grade X SMAN 6 Kediri. This study was conducted in August and September of odd semester 2016/2017 academic year. This research was conducted by quasi-experimental research subjects in class X-9 and X-10. Parameters measured were critical thinking skills that are measured using posttest essay. The results were analyzed using critical thinking skills t test showed the t-test calculation results obtained Sig. (2-tailed) 0.000 <0.05. This means there is significant influence learning model combined Student Problem Based Learning Facilitator And Explaining to students' critical thinking skills matter Kingdom Fungi